То the problem of investigation of language as an informational structure - Baluta, Galyna (Actual Problems of Mind, 2017)
The paper outlines a variant of resolving a problem of investigation of language as the third ontological dimension (side by side with the physical one and mental one) and a unity of being and thought, genetic informational code. The main point of the paper is the postulation of the idea of prospectivity of phenomenological, structural and psycho-analytic approaches to the consideration of interrelations between language and reality in the light of the classical polemics between Plato and Aristotle.